2021
DOI: 10.1177/23259671211062929
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Tendon Regeneration After Application of Purified Exosome Product: An In Vivo Study

Abstract: Background: Tendons are primarily acellular, limiting their intrinsic regenerative capabilities. This limited regenerative potential contributes to delayed healing, rupture, and adhesion formation after tendon injury. Purpose: To determine if a tendon’s intrinsic regenerative potential could be improved after the application of a purified exosome product (PEP) when loaded onto a collagen scaffold. Study Design: Controlled laboratory study. Methods: An in vivo rabbit Achilles tendon model was used and consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 51 publications
(108 reference statements)
0
45
0
Order By: Relevance
“…While the neuroregenerative effect of exosomes has recently been highlighted and their application in tissue regeneration (i.e., bone, wound, and tendon) has been increasingly investigated, little is known about the mechanisms of action of exosomes (Ikumi et al, 2021;Kisby et al, 2021;Ren et al, 2021;Shi et al, 2021Shi et al, , 2023Wellings et al, 2021). In this study, a PEP dose-response analysis was successfully investigated and examined effects of neurite outgrowth in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the neuroregenerative effect of exosomes has recently been highlighted and their application in tissue regeneration (i.e., bone, wound, and tendon) has been increasingly investigated, little is known about the mechanisms of action of exosomes (Ikumi et al, 2021;Kisby et al, 2021;Ren et al, 2021;Shi et al, 2021Shi et al, , 2023Wellings et al, 2021). In this study, a PEP dose-response analysis was successfully investigated and examined effects of neurite outgrowth in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The exosomes are lyophilized and stored as a stabilized powder cake in glass vials at RT. PEP may have a great potential to enhance tissue repair and regeneration (Ikumi et al, 2021;Kisby et al, 2021;Ren et al, 2021;Shi et al, 2021Shi et al, , 2023Wellings et al, 2021) protein-1, hepatocyte growth factor, and vascular endothelial growth factor (Ikumi et al, 2021). Peripheral nerve basic science research using MSCs has been greatly studied over the past decades.…”
Section: Discussionmentioning
confidence: 99%
“…More organized and denser collagenous tissue and fewer inflammatory cells were also displayed at the tendon-bone interface after rotator cuff repair in the TISSEEL–PEP group [ 90 ]. Wellings et al demonstrated significantly fewer external adhesions and improved mechanical functions with the application of PEP loaded onto a collagen scaffold, indicating that the off-the-shelf PEP product favored intrinsic healing instead of extrinsic healing [ 91 ].…”
Section: Exosomes In Tendon and Repair And Regenerationmentioning
confidence: 99%
“…Based on the mechanisms, many studies have established bio-engineered exosomal products that show benefits to soft tissue wound healing as listed in Figure 1 (right). Among them, PEP can significantly enhance both tendon [ 74 , 91 ] and peripheral nerve [ 184 ] regeneration, but has not been studied on skeletal muscles. Future studies regarding PEP’s effects on muscle repair can be useful.…”
Section: Future Directionsmentioning
confidence: 99%
“…Supplementation of collagen with purified exosome product demonstrated intrinsic healing in tendon disorder. Application of exosomes for tendon injury show less microscopic and macroscopic circumferential adhesions [ 143 ]. BM-MSC-derived exosomes loaded with fibrin glue enhance the expression of tenomodulin and type 1 collagen, improve the biomechanical properties of neotendon, and facilitate the differentiation and proliferation of resident stem cells into local TSCs in vivo [ 144 ].…”
Section: Orthobiologics In Atmentioning
confidence: 99%